Abiraterone acetate for metastatic castration‐resistant prostate cancer after docetaxel failure: A randomized, double‐blind, placebo‐controlled phase 3 bridging study. (15th February 2016) - Sun, Yinghao; Zou, Qing; Sun, Zhongquan; Li, Changling; Du, Chuanjun; Chen, Zhiwen; Shan, Yuxi; Huang, Yiran; Jin, Jie; Ye, Zhang Qun; Xie, Liping; Lin, Guowen; et al.
Abstract : Objectives: To evaluate the efficacy and safety of abiraterone acetate‐prednisone versus placebo‐prednisone in Asian metastatic castration‐resistant prostate cancer patients who have failed docetaxel‐based chemotherapy. Methods: In this double‐blind, phase 3 study from China, 214 patients were randomized (2:1) to abiraterone acetate 1000 mg once daily plus prednisone 5 mg twice daily and placebo plus prednisone 5 mg twice daily in 28‐day treatment cycles. Results: Abiraterone acetate–prednisone treatment significantly decreased prostate‐specific antigen progression risk by 49%, with longer median time to prostate‐specific antigen progression of 5.55 months versus 2.76 months in the placebo‐prednisone group (hazard ratio 0.506, P = 0.0001, primary end‐point). There was a strong trend for improved overall survival in the abiraterone acetate–prednisone group, with a 40% decrease in the risk of death (hazard ratio 0.604, P = 0.0597); however, median survival was not reached in either group because of the short follow‐up period (12.9 months) and limited number of observed death events. The prostate‐specific antigen response rate was higher in the abiraterone–prednisone group (49.7%) than in the placebo–prednisone group (14.1%). A total of 37.1% patients in this group had pain progression events compared with 50.7% in the placebo–prednisone group. Abiraterone–prednisone significantly decreased the risk of pain progression by 50% (hazard ratio 0.496, P = 0.0014). The incidence of adverse events was similar between the two groups; the most common adverse events being anemia (25.9% for abiraterone–prednisone vs 22.5% for placebo–prednisone), hypokalemia (25.9% and 11.3%), bone pain (23.8% and 21.1%), hypertension (16.1% and 12.7%) and increased aspartate aminotransferase (14.7% and 15.5%), respectively. Conclusions: Abiraterone–prednisone significantly delays disease and pain progression, and prostate‐specific antigen, with a favorable benefit–risk ratio in Asian metastatic castration‐resistant prostate cancer patients in the post‐docetaxel setting.